Edukasi Pencegahan Covid-19 Berbasis Video bagi Remaja di Rumah Yatim Bina Anak Sholeh - Khodijah Khodijah; Ita Nur Itsna; Anisa Oktiawati (Jurnal Abdimas Kesehatan (JAK), 2021)
Coronavirus is a group of viruses that can cause disease in animals or humans. Several types of coronavirus are known to cause respiratory infections in humans ranging from coughs and colds to more serious ones such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). One way that can be done to help the government break the increasing chain of COVID-19 transmission is to get used to the implementation of Clean and Healthy Behavior (PHBS) in all groups, both parents and children. The results of interviews with adolescents at the Bina Anak Sholeh Orphanage showed that they had not received clear information on COVID-19 prevention, so they wanted information about COVID-19 directly. Objective: Increase knowledge of adolescents about the prevention of COVID-19 based on video for teenagers at the Sholeh orphanage. Method: Implementation of community service by providing education to adolescents with COVID-19 prevention videos was held on Thursday, October 8, 2020. Results: The results of the evaluation of the activities that have been carried out show that youth are very enthusiastic about participating in extension activities from beginning to end. The results of the questions and answers carried out by the moderator after the delivery of counseling materials confirmed that most participants had understood the COVID-19 material and that they could re-practice proper hand washing as a form of prevention from COVID-19. Conclusion: This service is expected to be able to increase knowledge about the prevention of COVID - 19 and be able to implement clean and healthy living habits in everyday life